(3ecGJjH hCTYGQs - (3GHf ecGfS , YHO GdQMef Hf YHO GdQRGb Hf EHQGgje, aNQ GdOjf CHh GdaQL,J (B794 (3g` s
(3ChdgG (B:s
(3cJH GdUGMH aNQGdOjf Hf ecGfS dTeS GdOjf GdeJfHi cJH GdbJd hGdbJGd YdjfG hYdi GdZGfjGJ LQ GdPjhd s
(3BNQgG (B:s
(3BNQ GdhLhO efgG jSWh GdSja bGWY ajGJQi ef Sfg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdNW ajg HYV VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B101 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs